Pembelajaran IPS Melalui Permainan Galah Aceh di Sekolah Menengah Pertama Negeri 8 Pidie Jaya - Mursyidah, Mursyidah; Mukhlis, Mukhlis (SCAD Independent, 2025)
The aim of the study to determine the increase in the creativity of social studies teachers in each learning process and to improve student learning outcomes through the Galah Aceh game by utilizing the pase card in social studies learning. The research method used is classroom action research. The results obtained are improving student learning outcomes from cycle I to cycle III. In the first cycle, the average result obtained was 71.2, increasing to 80.08 in the second cycle and in the third cycle, it increased again by 89.24. The conclusion of this study is that social studies learning through the Galah Aceh game using the pen pase media can increase the creativity of social studies teachers in every learning process and improve student learning outcomes through social studies learning.